Evaluation of programmatic changes to an antimicrobial stewardship program with house officer feedback. Issue 2 (15th March 2012) - Hong, Steven Y.; Epstein, Lauren H.; Lawrence, Kenneth; Davidson, Lisa; Taur, Ying; Nadkarni, Lauren; Doron, Shira
Abstract Rationale, aims and objectives A collegial relationship between prescribers and antimicrobial stewards, along with an appreciation of the importance of antimicrobial stewardship, is essential for optimal functioning of an antimicrobial stewardship program (ASP). Programmatic adjustments based on feedback may be beneficial to the success of ASPs. The objective of this study is to assess the experience of house officers with the ASP and the effect of programmatic improvements. Methods A survey of house officers at an academic medical centre was conducted assessing their experience with the ASP before (2008) and after (2010) programmatic interventions were instituted. Results Of 225 house officer surveys sent, we received 97 responses (88% from medical doctors). The majority indicated that ASP was either very or somewhat important in fighting antibiotic resistance (100%), improving patient care (97%), preventing medication errors (91%) and containing health care costs (89%). Ninety‐one per cent indicated either a very good or good educational experience with the ASP. The ASP often reminded respondents of a patient's allergy (31%), to adjust for renal function (78%), and 38% were prevented from making a medication error. Comparing 2008 and 2010, a higher proportion of respondents in 2010 said they had a very good or good educational experience with ASP [84% versus 98%, odds ratio (OR) = 8.40, P = 0.022] and a lower proportion of respondents reported confusion about ASP procedures (59% versus 39%, OR = 0.43, P = 0.048). Conclusions House officer feedback resulted in ASP policy changes which improved the ASP experience.